Modeling the viscosity of silicate melts containing manganese oxide - Kim Wan-Yi; Pelton Arthur D.; Bale Christopher W.; Bélisle Eve; Decterov Sergei A. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2013)
Our recently developed model for the viscosity of silicate melts is applied to describe and predict the viscosities of oxide melts containing manganese oxide. The model requires three pairs of adjustable parameters that describe the viscosities in three systems: pure MnO, MnO-SiO2 and MnO-Al2O3-SiO2. The viscosity of other ternary and multicomponent silicate melts containing MnO is then predicted by the model without any additional adjustable model parameters. Experimental viscosity data are reviewed for melts formed by MnO with SiO2, Al2O3, CaO, MgO, PbO, Na2O and K2O. The deviation of the available experimental data from the viscosities predicted by the model is shown to be within experimental error limits.